MODERN PHARMACOTHERAPY OF THE STABLE ANGINA: POSSIBILITIES AND PROSPECTS OF NICORANDIL IMPLEMENTATION - Z. M. Sizova; E. V. Shikh; V. L. Zakharova; E. V. Smirnova (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To evaluate antianginal efficacy and safety of nicorandil for angina attack prevention and relief in patients with ischemic heart disease (IHD) and symptoms of stable angina class 2-3.Material and methods. 30 patients with stable angina class 2-3 (17 men, 13 women; aged 58.6±5.8 y.o.) were included into the study. All patients received amlodipine 10 mg QD within 2 weeks. For angina attack relief patients used nicorandil 10-20 mg and in case of its inefficacy — nitroglycerin. In 2 weeks all patients were randomized in 2 groups. Patients of the 1st group (n=15) received nicorandil 20 mg TID, patients of the 2nd group (n=15) — amlodipine 10 mg QD. The study duration was 3 months. The efficiency evaluation was based on the analysis of hemodynamic indicators (heart rate, blood pressure), bioelectric heart activity (electrocardiogram), velocity exercise tolerance test, ambulatory blood pressure monitoring indicators. The pain severity was defined with Borg's scale, and the quality of life — with General Health Questionnaire (GHQ-28). Therapy safety was evaluated in according to laboratory tests results.Results. Frequency of angina attacks reduced by 60% (р<0.05) and 47% (р<0.05) in 12 weeks of nicorandil and amlodipine therapy, respectively. Duration of angina decreased by 38% and 37% (р<0.05) in 12 weeks of nicorandil and amlodipine therapy, respectively. Eexercise duration before angina attack onset increased by 56% (р<0.05) in 1 month of nicorandil therapy. A number of myocardial ischemia episodes reduced by 64% (р<0.05) and 54% (р<0.05) due to nicorandil and amlodipine therapy, respectively. General GHQ-28 score decreased by 54% (р<0.05) and 44% (р<0.05) in patients of the 1st and the 2nd groups, respectively. Tolerability of nicorandil was good in 13 (86.7%) and satisfactory in 2 (13.3%) patients.Conclusion. Nicorandil can be prescribed both for the prevention and for relief of angina attacks in IHD patients.